Математичне моделювання процесу біологічного очищення забруднених вод як об’єктa автоматичого керування - Гончаренко, Б. М.; Лобок, О. П.; Сич, М. А.; Віхрова, Л. Г.; Goncharenko, В.; Lobok, О.; Sych, M.; Vihrova, L. (ЦНТУ, 2017)
Наведені та обґрунтовані прийняті припущення при складанні математичної моделі процесу. Представлена і розглянута структурно-параметрична схема технологічного процесу біологічного очищення забруднених вод. Наведена в диференціальному вигляді математична модель та дані роз’яснення складових. Вибрані вхідна (керувальна) та вихідна (керована) величини моделі за каналом керувального діяння. З метою подальшого полегшення розв’язку наводяться вираз математичної моделі у векторному вигляді та вираз керованої величини. Проведена лінеаризація моделі та наведений її лінеаризований вигляд. Наведені вирази дискретних операторів критерія якості керування процесом очищення, дробового - регулятора та системи керування вцілому. Наведені результати чисельного моделювання системи керування процесом очищення води на основі розробленої моделі. The assumptions made in the compilation of the mathematical model of the process are given and justified. The structural-parametric scheme of the technological process of biological treatment of polluted waters is presented and considered. A mathematical model is given in a differential form and explanations of its components are given. The input (control) and output (controlled) values of the model along the control action channel are selected. The expression of the mathematical model in vector form and the expression for the controlled quantity are given for further facilitating the solution. The linearization of the model is carried out and its linearized form is given. Expressions of discrete operators of the quality criterion for control of the cleaning process, fractional regulator and control system are given. The results of numerical simulation of the water treatment process control system based on the developed model are presented. The degree of efficiency in the application of fractional regulators as part of the automatic control system based on classical mathematical model of the process and the reasons for the high sensitivity of optimality criterion and transients on the order of fractional derivatives and integrals require further research.
Mathematical modeling of the process of biological purification of polluted waters as an object of automatic control
Keywords: біологічне очищення води; математичне моделювання; оптимальне керування; чисельне моделювання; дробовий регулятор; biological water purification; mathematical modeling; optimal control; numerical simulation; fractional regulator